Abiotic reductive dechlorination of chlorinated ethylenes by iron-bearing phyllosilicates - Lee, WJ; Batchelor, B (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Abiotic reductive dechlorination of chlorinated ethylenes (tetrachloroethylene (PCE), trichloroethylene (TCE), cis-dichloroethylene (c-DCE), and vinylchloride (VC)) by iron-bearing phyllosilicates (biotite, vermiculite, and montmorillonite) was characterized to obtain better understanding of the behavior of these contaminants in systems undergoing rernediation by natural attenuation and redox manipulation. Batch experiments were conducted to evaluate dechlorination kinetics and some experiments were conducted with addition of Fe(II) to simulate impact of microbial iron reduction. A modified Langmuir-Hinshelwood kinetic model adequately described reductive dechlorination kinetics of target organics by the iron-bearing phyllosilicates. The rate constants stayed between 0.08 (+/-10.4%) and 0.401(+/-8.1%) day(-1) and the specific initial reductive capacity of iron-bearing phyllosilicates for chlorinated ethylenes stayed between 0.177 (+/-6.1%) and 1.06 (+/-7.1%) muM g(-1). The rate constants for the reductive dechlorination of TCE at reactive biotite surface increased as pH (5.5-8.5) and concentration of sorbed Fe(II) (0-0.15 mM g(-1)) increased. The appropriateness of,the model is supported by the fact that the rate constants were independent of solid concentration (0.0085-0.17 g g(-1)) and initial TCE concentration (0.15-0.60 mM). Biotite had the greatest rate constant among the phyllosilicates both with and without Fe(H) addition. The rate constants were increased by a factor of 1.4-2.5 by Fe(II) addition. Between 1.8% and 36% of chlorinated ethylenes removed were partitioned to the phyllosilicates. Chloride was produced as a product of degradation and no chlorinated intermediates were observed throughout the experiment. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: HENRYS LAW CONSTANTS; CARBON-TETRACHLORIDE; GREEN RUST; TRANSFORMATION; SULFIDE; MINERALS; KINETICS